Response to Dissociation Between Severity of Takotsubo Cardiomyopathy and Presentation With Shock or Hypotension. Issue 10 (8th August 2013) - Yalcinkaya, Emre; Celik, Murat; Yuksel, Uygar; Yildirim, Erkan; Bugan, Baris
<x xml:space="preserve">Abstract</x> Chong CR et al. Clin Cardiol. 2013;36:401–406